CONSERVATION OF SOUTH AFRICAN MEDICINAL PLANTS: TOOLS FOR THE FUTURE - van Staden, J.; Light, M. E. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The extensive use of medicinal plants worldwide is increasing and there has been much emphasis on the potential for discovering novel drugs from these natural resources. Along with this interest in the development of traditional medicine is the need for propagation and improved cultivation methods for heavily utilized medicinal plants. This is particularly important for those species which are over-exploited and have become severely depleted in the wild. In South Africa, it is estimated that as much as 70 000 tonnes of plant material is consumed per year [1]. Thus, the provision of plants for re-introduction into natural areas and as alternative plant sources for the production of medicinal plant material for sale through informal markets and larger commercial concerns is an important strategy for the conservation of medicinal plants. Several studies related to aspects of seed germination, in vitro propagation and cultivation of medicinal plants for small-scale farming have been conducted in our Research Centre. This presentation will highlight some examples of our research in this field and discuss some of the problems facing the cultivation and conservation of medicinal plants in South Africa. Acknowledgements: National Research Foundation (NRF, Pretoria), University of KwaZulu-Natal. 1. Mander, M. & Le Breton, G. (2006) Overview of the medicinal plants industry in southern Africa. In Diederichs, N. (Ed.) Commercialising Medicinal Plants: A Southern African Guide. Sun Press, Stellenbosch, South Africa. pp. 1-8